ANALISIS KORELASI ANTARA MATERI GEOMETRIBANGUN DATAR PADA PEMBELAJARAN MATEMATIKA DI SEKOLAH DENGAN MATERI OSN MATEMATIKA TINGKAT SEKOLAH MENENGAH PERTAMA - Hartatik, Sri; Herlambang, Teguh (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2017)
His study aimed to describe the correlation between matter Geometry Build Flat in school with OSN material Mathematics at Junior Secondary Level. This research is a qualitative research. The data used in this research is primary data secondary data. Primary data is the result of OSN problem solving tests mathematics students of SMPN 32 Surabaya and secondary data referred to in this ppenelitian is OSN Mathematics Test Bank district / city level in 2015. The aim of this study to analyze the suitability of the material geometry on matters Olympics SK and KD mathematics curriculum in 2013. Based on data analysis, for OSN math question bank, there are 6 questions of 25 questions that there is a matter of waking up flat geometry. From the analysis to the six questions OSN Mathematics Geometry Flat material was found that from about the existing 6, 5 question does not comply with the existing KD while the first question in accordance with KD in 2013. Based on the type of curriculum about five questions included in nonroutine matter while 1 question belong to a routine matter. Based on the linkage problem, almost the entire matter related to some of the concepts that students are expected to link the concept that there is thus obtained the expected solution.